Loss of EpCAM expression in breast cancer derived serum exosomes: role of proteolytic cleavage - Rupp, Anne-Kathleen; Rupp, Christian; Keller, Sascha; Brase, Jan C.; Ehehalt, Robert; Fogel, Mina; Moldenhauer, Gerhard; Marmé, Frederik; Sültmann, Holger; Altevogt, Peter (Gynecologic oncology, 2011)
Objective - Cancer cells in the body release soluble and membranous factors that manipulate the tumor environment to facilitate growth and survival. Recent years have provided evidence that small microvesicles that are termed exosomes may play a pivotal role in this process. Exosomes are membrane vesicles with a size of 40-100nm that are released by both tumor and normal cells and can be found in various body fluids. Tumor-derived exosomes carry functional proteins, mRNAs, and miRNAs and could serve as novel platform for tumor diagnosis and prognosis. However, marker proteins that allow enrichment of tumor-derived exosomes over normal exosomes are less well defined. - Methods - We used Western blot analysis and antibody coupled magnetic beads to characterize CD24 and EpCAM as markers for exosomes. We investigated ovarian carcinoma ascites, pleural effusions and serum of breast carcinoma patients. As non-tumor derived control we used exosomes from ascites of liver cirrhosis patients. - Results - Exosomes could be isolated from all body fluids and contained marker proteins as well as miRNAs. We observed that CD24 and EpCAM were selectively present on ascites exosomes of tumor patients and copurified together on anti-EpCAM or anti-CD24 magnetic beads. In breast cancer patients CD24 was present but EpCAM was absent from serum exosomes. Instead, the intact EpCAM ectodomain was recovered in a soluble form. We provide evidence that EpCAM can be cleaved from exosomes via serum metalloproteinase(s). - Conclusion - Loss of EpCAM on serum exosomes may hamper enrichment by immune-affinity isolation. We suggest that CD24 could be an additional marker for the enrichment of tumor-derived exosomes from blood.
Gesehen am 21.09.2022